The Reaction of N-Trimethylsilyl-Substituted Heteroarylamines with Esters and Thioesters: An Efficient Protocol To Access Diheteroarylamides - Koperniku, Ana; Zamiri, Maryam; Grierson, David S. (Synthesis, 2019)
The S-benzyl thioester and methyl ester derivatives of a representative 4-pyridinone-based carboxylic acid were sufficiently activated to react efficiently in amide coupling reactions with the amide anion generated in situ from the N-trimethylsilyl derivative of different weakly nucleophilic heteroarylamines. In acetonitrile as solvent, the precipitated diheteroarylamide products were isolated in pure form by vacuum filtration. This simple amide bond forming protocol can be readily adapted to the parallel synthesis of compound libraries.
Keywords: amide coupling; diheteroarylamides; N-trimethylsilyl activation; thioesters; esters; parallel synthesis